Level of satisfaction among industrial customers in relation to logistics service provider in Sabah - Al Nasrie Weli; Sidah Idris; Abdul Rahman Yaakob (Universal Publishers, 2020)
To investigate the relationship between operational logistics service quality (OLSQ) and relational logistics service quality (RLSQ) towards customer satisfaction among industrial customer in Sabah. self-administrative survey and online survey questionnaire were used to collect the data for this study. List of 180 industrial customer provided by the express bus companies. Purposive sampling techniques was used in this study. The data was analyzed using SPSS 26.0 and SmartPLS 3.0. Results support the hypothesis developed in this study confirming that service perceptions lead to customer satisfaction among industrial customer in Sabah. The current study is limited to east Malaysia which is Sabah where it excluded the respondent from peninsular of Malaysia. Besides, present study focusing only on land logistics transportation and excluded the air and ocean logistics transportation. Those involved in logistics especially express bus managers can find new methods to make their customers satisfied and place their trust on the service provided. Not only that, as the express bus was used to send parcels within the various districts in Sabah, this present study can be used as a reference tool by the policy makers to revisit and improve the existing policies in the future. For the record, this study is the first of its kind ever conducted in Sabah. It shows that OLSQ and RLSQ is an important indicator in satisfying industrial customers in the express bus sector.